Modulation of Premetastatic Niche by the Vascular Endothelial Growth Factor Receptor Tyrosine Kinase Inhibitor Pazopanib in Localized High‐Risk Prostate Cancer Followed by Radical Prostatectomy: A Phase II Randomized Trial. (1st November 2018) - Maughan, Benjamin L.; Pal, Sumanta K.; Gill, David; Boucher, Kenneth; Martin, Christopher; Salgia, Meghan; Nussenzveig, Roberto; Liu, Ting; Hawks, Josiah L.; Batten, Julia; Nachaegari, Gayatri; Stephenson, Robert; et al.
Abstract: Lessons Learned: Pazopanib was not effective in altering the premetastatic niche in the neoadjuvant setting. Pazopanib was safe and well tolerated without any new safety signals. Background: Vascular endothelial growth factor receptor 1 (VEGFR1) expressing myeloid‐derived suppressor cells (VEGFR1+ MDSCs) potentially foster metastases by establishing a premetastatic niche. In a preclinical study, VEGFR1+ clustering in lymph nodes (LNs) independently predicted time to biochemical recurrence (TTBR) in localized prostate cancer [1 ]. The hypothesis was that neoadjuvant pazopanib therapy will decrease VEGFR1+ clusters in pelvic lymph nodes and improve outcomes. Methods: This is a phase II trial (NCT01832259) of neoadjuvant pazopanib 800 mg versus placebo daily for 4 weeks in high‐risk localized prostate cancer. The primary endpoint was a decrease in VEGFR1+ MDSC clustering assessed by immunohistochemistry (IHC) analysis. Secondary endpoints were safety, feasibility, and TTBR. Results: Thirty patients were randomized to pazopanib versus placebo, with 15 patients randomized to each arm. Demographic and disease characteristics were similar in both arms. There was no difference in the VEGFR1+ clustering between the treatment arms (p = .345). Neoadjuvant therapy with pazopanib was well tolerated, and surgical complications were similar in both arms. Conclusion: Neoadjuvant pazopanib therapy did not alter the premetastatic niche; however, treatment targeting vascular endothelial growth factor (VEGF) in the preoperative period was safe and feasible, which may open up the avenue to investigate novel combinatorial regimens, including a VEGF inhibitor in combination with immune checkpoint inhibitor in this setting.